Prevalence of dental caries among children of SOS children's village in Croatia - Ivanišević Zrinka; Matijević Marko; Užarević Zvonimir; Petrović Đorđe; Jurlina Davor; Jerolimov Vjekoslav (Vojnosanitetski Pregled)
Background/Aim. Oral health is an integral part of general health and an important factor in the overall quality of life. The purpose of this study was to investigate the prevalence of dental caries among the children from the SOS Children’s Village in Croatia. Methods. The dental examinations based on the World Health Organization criteria were performed on 88 children from SOS Children’s Village in Croatia. The teeth were clinically examined with standard dental instruments using the visual-tactile method under standard light. The clinical indexes of decayed, missed, and filled (dmft and DMFT, for primary and permantnt teeth, respectively) and decayed, missed, and filled surfaces (DMFS), as well as the significant caries index (SiC) were recorded. Results. Among the children from the SOS Children’s Village caries incidence were 57.94%. The mean dmft, DMFT and DMFS of all children was 1.82, 1.90 and 2.82, respectively. The highest mean dmft and DMFT score of 4.24 and 2.56 was found among 7–10 and 11–14 years old children, respectively. The highest mean DMFS score of 3.85 and 3.90 was found among 11–14 years old children and among the children from the SOS Children’s Village Lekenik, respectively. Among all children, the SiC index was 4.69. There was a significant difference between age groups and children’s place of residence in DMFT, DMFS and SiC. Conclusion. Prevalence of dental caries is low among the children from the SOS Children’s Village in Croatia compared to the children who lived with biological families.